CoSimPy: An open-source python library for MRI radiofrequency Coil EM/Circuit Cosimulation. (April 2022) - Zanovello, Umberto; Seifert, Frank; Bottauscio, Oriano; Winter, Lukas; Zilberti, Luca; Ittermann, Bernd
Highlights: Open-source Python library for EM/Circuit cosimulations. Optimised for Magnetic Resonance Imaging, radiofrequency coils design. Methods for Electromagnetic field distributions and Touchstone files automatic import and export. Methods for radiofrequency coils performance evaluations. Abstract: Background and objectives: The Electromagnetic/Circuit cosimulation method represents a valuable and effective strategy to address those problems where a radiative structure has to interact with external supporting circuitries. This is of particular concern for Magnetic Resonance Imaging (MRI), radiofrequency (RF) coils design, where the supporting circuitry optimisation represents, generally, a crucial aspect. This article presents CoSimPy, an open-source Python circuit simulation library for Electromagnetic/Circuit cosimulations and specifically optimised for MRI, RF coils design. Methods: CoSimPy is designed following an Object-orientated programming. In addition to the essential methods aimed to performed the Electromagnetic/Circuit cosimulations, many others are implemented both to simplify the standard workflow and to evaluate the RF coils performance. In this article, the theory which underlies the fundamental methods of CoSimPy is shown together with the basic framework of the library. Results: In the paper, the reliability of CoSimPy is successfully tested against a full-wave electromagnetic simulations involving a reference setup. The library is made available under https://github.com/umbertozanovello/CoSimPy together with a detailed documentation providing guidelines and examples. CoSimPy is distributed under the Massachusetts Institute of Technology (MIT) license. Conclusions: CoSimPy demonstrated to be an agile tool employable for Electromagnetic/Circuit cosimulations. Its distribution is meant to fulfil the needs of several researchers also avoiding duplication of effort in writing custom implementations. CoSimPy is under constant development and aims to represent a coworking environment where scientists can implement additional methods whose sharing can represent an advantage for the community. Finally, even if CoSimPy is designed with special focus on MRI, it represents an efficient and practical tool potentially employable wherever electronic devices made of radiative and circuitry components are involved.